2019
DOI: 10.14202/vetworld.2019.1998-2006
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of six molecular typing methods as epidemiological tools for the study of Salmonella isolates in two Colombian regions

Abstract: Aim: The aim of this study was the genotypic characterization of the strains of Salmonella spp. isolated from broiler chickens and humans with gastroenteritis from two regions of Colombia, by BOXA1R-polymerase chain reaction (PCR) and random amplification of polymorphic DNA (RAPD)-PCR methods. Materials and Methods: Forty-nine strains of Salmonella were assessed, 15 from poultry farms in Santander region, and 34 from Tolima region isolated from poultry farms (n=24) and the stool samples of people with gastroe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Our research group has reported the antibiotic resistance patterns of Salmonella spp. in poultry production as well as in other sectors in Colombia, as characterized by different genotyping methods [10][11][12][13][14][15]. However, these studies did not address the molecular mechanisms associated with resistance to quinolones and fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has reported the antibiotic resistance patterns of Salmonella spp. in poultry production as well as in other sectors in Colombia, as characterized by different genotyping methods [10][11][12][13][14][15]. However, these studies did not address the molecular mechanisms associated with resistance to quinolones and fluoroquinolones.…”
Section: Introductionmentioning
confidence: 99%
“…RAPD-PCR has been extensively used to study the epidemiology and taxonomy of Enterobacteriaceae, including important human pathogens like Escherichia coli, Klebsiella pneumoniae, and Salmonella spp. It has also been employed to investigate the genetic diversity of these bacteria in various environmental niches, such as soil, water, and food (31)(32)(33). The results of genotyping isolates using RAPD-PCR showed that, although when calculating the performance of the genotyping method using the 1254 primer, Simpson's index shows a relatively respectable result, there was a significant relationship between RAPD genotype and Salmonella serotype, and 16 isolates (26.66%) could not be successfully genotyped using this method, which can be significant.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthily, the profiles assigned by the three genotyping methods and their combinations were able to describe a specific fingerprint for each serotype, agreeing with the previous serotyping of the isolates, and allowed us to describe intraserovar differentiations that are not perceivable with serotyping. Similarly, PCR-based genotyping methods have been previously used to differentiate Salmonella enterica strains at and below serotype level (7,25). However, our purpose is not to replace but to complement the traditional typing methods for Salmonella enterica to provide valuable data regarding the relationships within isolates, information that can be used in epidemiological surveillance.…”
Section: Discussionmentioning
confidence: 99%